2017
DOI: 10.15406/ijcam.2017.06.00201
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Actions on Cell Differentiation, Proliferation and Inflammation

Abstract: The most well-known function of vitamin D (1,25-(OH) 2 D 3 ) is to maintain calcium and phosphate homeostasis and promote bone mineralization. However, apart from these traditional calcium-related actions, 1,25-(OH) 2 D 3 is being increasingly recognized for its potent antiproliferative, pro-differentiation, and immunomodulatory roles. Along with these non-calcemic or non-classic actions of 1,25-(OH) 2 D 3 , new therapeutic actions of 1,25-(OH) 2 D 3 have been discovered in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Many genes are regulated by the active form of vitamin D (1,25dihydroxyvitamin D) in tissues such as the immune system, bone, muscles, lungs, heart, and kidney, among others. Although its primary biological action, which is mediated by vitamin D receptor (VDR), is to regulate serum calcium levels and promote bone mineralization, several studies have described vitamin D as a potent non-proliferation, pro-differentiation and immunomodulation factor [1]. Its precursor, 25-hydroxyvitamin D (25(OH)D) is the circulating form of vitamin D which is considered the best marker to assess vitamin D levels [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Many genes are regulated by the active form of vitamin D (1,25dihydroxyvitamin D) in tissues such as the immune system, bone, muscles, lungs, heart, and kidney, among others. Although its primary biological action, which is mediated by vitamin D receptor (VDR), is to regulate serum calcium levels and promote bone mineralization, several studies have described vitamin D as a potent non-proliferation, pro-differentiation and immunomodulation factor [1]. Its precursor, 25-hydroxyvitamin D (25(OH)D) is the circulating form of vitamin D which is considered the best marker to assess vitamin D levels [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin D receptor (through which calcitriol achieves its functions) was believed to be exclusively endocrine, coupling with retinoic X receptor to form a heterodimer, subsequently binding to response elements in the promoter regions of target genes and exerting effects related to mineral metabolism (24). Recent research has shown that the vitamin D receptor is expressed in tissues of multiple origin which could explain its varying effects such as immunomodulation, cell proliferation and differentiation (25,26). Further, a cytoplasmic form of the vitamin D receptor has been identified that responds rapidly or non-genomically to calcitriol and is thought to be involved in cellular calcium handling and other processes (24,27).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is now being known for its potential antiproliferative, pro-differentiation and immunomodulatory roles. It can regulate cell differentiation and growth by binding to the VDF's that are found in most body cells [10].…”
Section: Regulation Of Cell Differentiation and Growthmentioning
confidence: 99%